Establishing engineering S-curves to evaluate supervision engineer allocations for highway construction projects - Wang, Shih-Hsu; Wang, Wei-Chih; Hsu, Pei-Yuan; Chen, Ci-Hao; Wang, Kun-Chi (Journal of Civil Engineering and Management, 2016)
An engineering consultant firm needs to allocate engineers to supervise a highway construction project in each month during the construction phase. Properly assigning the supervision engineers under a cost-plus-fixed-fee contract has been a key factor affecting the profitability of the firm and the quality assurance of the project. Assigning too many engineers will be a waste, while allocating too few engineers may harm the supervision quality. This work proposes a two-stage model to develop engineering S-curves (called ES-curves) for planning and controlling the engineering supervision schedule. In the planning stage, a predictive ES-curve model is established based on historical ES-curves. In the controlling stage, an ES-curve is built according to the relationships between the engineering progress and construction progress. A cluster analysis and regression analysis are applied to the model development. A case study demonstrates that the produced ES-curves can help management in planning and evaluating when to increase or decrease the number of supervision engineers assigned to a project.